NEW RECORDS OF MARINE PARASITIC MOLLUSCS FROM ANDAMAN AND NICOBAR ISLANDS, INDIA - Narayana, Sumantha (Journal of the Bombay Natural History Society (JBNHS), 2023)
Three parasitic gastropod species – Melanella bovicornu Pilsbry, 1905; Prosimniasemperi Weinkauff, 1881 and Epidendriumaureum Gittenberger and Gittenberger, 2005 – are recorded for the first time from the Indian waters of the Andaman and Nicobar Islands. Brief species descriptions and their host association are provided.